Religius Radikal: Ekspresi Gen-Z dalam Kesadaran Beragama dan Aktualisasi Ketaatan di Kalimantan Selatan - Noor Hasanah; Huriyah (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2023)
The interpretation, understanding, and practice of Islam have always been subject to diversity, with some adherents adopting a rigid, textual, and even "ferocious" stance, leading to their characterization as intolerant, extreme, radical, and even terrorist. In contrast, others adopt a softer, more flexible, and contextual approach. A pivotal factor influencing this distinction is the method of information acquisition. The Generation Z (Gen-Z) cohort, born between 1995 and 2012, is currently entering the prepubertal and pubertal phases of self-identity exploration and ideological turmoil. As the digital generation, they are immersed in an era of abundant information, including that pertaining to Islam. On the one hand, this heightened religious consciousness motivates Gen-Z to strive for piety by studying Islam through various means; on the other hand, the pursuit of piety is rigid and not local, suggesting a religiousness that is also radical.This research was conducted in South Kalimantan among a sample of Gen-Z aged 18-24 who are students. The objective of this study is to ascertain the degree to which Gen-Z in South Kalimantan appreciate and actualize wasathiyah Islam, or, conversely, whether they are religious but radical.This research is of an exploratory nature, employing a field study approach.The data collected through questionnaires addressed the level of religious consciousness, the manner in which values and Islamic teachings are lived, the means of expressing Islam, and the sources of Islamic learning utilized.The data was analyzed through simple statistical calculations and presented descriptively as a measurement of central tendency. The results indicate that, in general, Gen-Z members do not recognize the radical tendencies in their views and attitudes, particularly within a Muslim-majority community. Keywords: Religious, Radical, Gen-Z, Religious Consciousness, Actualization of Piety